Maternal and embryonic trace element concentrations and stable isotope fractionation in the smalleye smooth-hound (Mustelus higmani) - Ara?jo, Juliana de Souza (Elsevier, 2020)
Here, we evaluate maternal offloading of 16 trace elements (Essential: Co, Cr, Cu, Fe, Mn, Ni, Se and Zn; Nonessential: Al, As, Ba, Cd, Hg, Pb, Tl and U) and determine mother-offspring isotopic fractionation of ?13C and ?15N in muscle and liver tissue of four pregnant Mustelus higmani and 18 associated embryos sampled from the Amazon Coast of Brazil. Embryo muscle tissue had significantly higher concentrations of most trace elements when compared to mothers, with the exception of Hg. Embryo liver accumulated more nonessential elements than muscle (n = 7 vs. 0, respectively), while the Se:Hg molar ratio was >1 in liver and muscle of both mothers and embryos. Livers of embryos were moderately enriched in ?13C and ?15N when compared to that of their mother. Negative correlations were observed between embryo body length and ?13C and trace elements concentrations. We conclude that mothers offload a large portion of all essential elements and Al, As and Pb to their young and that the isotopic fractionation of embryos reflects maternal diet and habitat occupied, with ?13C diluted with embryonic growth. We also show that muscle and liver accumulate trace elements at different rates relative to the body length of embryos. The Se:Hg molar ratio suggests that Se could play a protective role against Hg toxicity during early stages of M. higmani embryonic development.